(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A body-worn camera is a gadget that is fastened to the chest of a police officer and captures audio and video that may be listened to and used as evidence. Police patrol officers typically use this equipment while doing their jobs. According to the study, body-worn cameras used by police officers during operations reduce ambiguity and promote transparency, according to both the community and police patrol personnel. Likewise, video recorded with a body-worn camera is admissible as proof in court if the rules and regulations are rigorously followed. Conversely, during police operations, body- worn cameras are simple to disarm and difficult to conceal. Similar to this, police personnel continue to film police operations using a different device, and not all police stations have body-worn cameras. The purpose of this study is to ascertain how the public and police patrol officers feel about the requirement to wear body camera.